Direitos fundamentais: o direito à paz no pensamento de Hannah Arendt: reflexões e propostas - Marques, Maria Edith de Azevedo (2010)
The development of the present paper has as objective a reflection on the right to peace in the classification of fundamental rights. The analysis of this intention lies in a reflection on the thinker Hannah Arendt, considered a fighter for the Jewish folk under Nazi persecution that culminated in the holocaust, in which millions of Jews were exterminated in an extremely cruel way. This violence against Jews made Hannah Arendt turn her life into a constant battle for peace with great determination in actions of courage and bravery. The peace we will talk about in this study refers to the peace not meaning the opposite of war but of violence, considering war a type of violence. We will briefly analyze two works of Hannah Arendt: ―The Origins of totalitarianism‖ and ―Eichmann in Jerusalem: a report on the banality of evil‖, also developing historical, social and politic aspects, about the facts that raised the interest of their author. Finally, we present the concept of peace within the juridical norm, talking about social peace that derives from the function of the right of harmonizing relationships between subjects